Factors Affecting Audit Delay (Case Study on Manufacturing Companies Listed on IDX) - Khansha Sindra Irfani (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
Company size, audit opinion, financial performance, and good corporate governance, were tested in this study to know the effect of these variables on audit delay. 159 sample data obtained through purposive sampling method from financial statements go public auditing manufacturing sector. The study used multiple linear regressions. The size of the company does not affect audit delays. While other variables such as audit opinions, financial performance, and corporate governance affect audit delay. This research contributes to reducing audit delays that can be used as consideration for the Financial Services Authority and subsequent research.